2020
DOI: 10.1111/jdv.16599
|View full text |Cite
|
Sign up to set email alerts
|

In‐depth prospection of Avène Thermal Spring Water reveals an uncommon and stable microbial community

Abstract: Background Avène Thermal Spring Water (TSW) exhibits therapeutic properties in the treatment of skin pathologies. Arising from a dolomitic aquifer system, its physico‐chemical properties are well‐established and its bacteriological quality regularly monitored. The microbiota of this aquifer have been characterized. Objectives We aimed to describe the structure of the bacterial community inhabiting the deep aquifer and to examine its dynamics over time. Methods The Avène TSW was collected at the catchment point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Such observations were made by Bourrain et al . [ 22 ] and Fasesan et al . [ 97 ] in recent years, with both groups pointing out that as-yet-undescribed taxa constitute a stable part of the microbial community in heavily used thermal waters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such observations were made by Bourrain et al . [ 22 ] and Fasesan et al . [ 97 ] in recent years, with both groups pointing out that as-yet-undescribed taxa constitute a stable part of the microbial community in heavily used thermal waters.…”
Section: Discussionmentioning
confidence: 99%
“…Underground water systems are ubiquitous and can serve as an insight into the subsurface microscopic world [ 17 ]. Their investigation provides an opportunity to uncover unique prokaryotic taxa in many places on Earth [ 18 22 ]. Amongst the most renowned localities are the hot springs of Yellowstone National Park, where culture-independent analyses have discovered numerous hitherto uncultured microorganisms, mostly novel clades of Archaea [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dysbalance of the skin microbiome can lead to an altered immune system, which can lead to inflammatory diseases of the skin. In Avène Thermal Spring Water were isolated 39 phylia (mainly Nitrospirae and Proteobacteria ) [ 38 ]. The mud can affect the microbiology of the skin, which has a beneficial effect on immune function (5 in vitro studies so far).…”
Section: Discussionmentioning
confidence: 99%
“…Bourrain et al [84] studied the structure of skin microbiome in patients with atopic dermatitis and its changes during an 18-day course of hydrotherapy with Avène spring water, finding that the number of lesional sites colonized by S. aureus, and the SCORAD index were significantly reduced, mainly in inflammatory and moist areas, promoting the emergence of a diversified microflora [83]. Later on, the same research group studied the microbial diversity of this thermal spring water and concluded that bacteria were distributed into 39 phyla, with Nitrospirae and Proteobacteria as the most prevalent.…”
Section: Thermal Spring Waters Microbiomementioning
confidence: 99%